Erklärungssequenzen in konsekutiv gedolmetschten Gesprächen - Jurewicz, Magdalena (Glottodidactica, 2001)
The paper presents a trial to define a phenomenon, called explanatory sequences, which accompanies conversations that are interpreted consecutively. These sequences pertain to the process of interpretation and they are interactive language activities, undertaken not only by the interpreter but also by both interlocutors in a crisis situation, which poses a threat of misunderstanding the message to be conveyed. The explanatory sequences belong to the language activities which pertain to the process of communication and aim to: organize the process of text production, correct the communication and do away with doubts. These activities are undertaken by the participants of the conversation which is led in one language. What is however important for our investigation, are the explanations which have been caused by the process of interpretation and the presence of the interpreter who acts as a language in-between. Explanations in the process of translation can also serve to signal a change of the code by the speaker, who himself translates his text to the target language.